Kejadian Stunting pada Balita: Studi Kasus di Desa Kebondalem, Kabupaten Pemalang - Mariza, Maya; Putriningtyas, Natalia Desy (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Stunting describes poor linear growth with z-score TB/U <-2SD. In 2020, Kebondalem Village had 27.9% stunting cases, exceeding provincial (27.7%) and national (26.9%). This study aims to analyze the relationship between risk factors and the stunting toddler incident in Kebondalem Village, Pemalang District, Pemalang Regency. Methods: This research is an observational quantitative analytic with a case-control design. Sampling using simple random sampling technique, with 49 cases and 49 controls. History of exclusive breastfeeding, acute diarrhea, family income per capita, and maternal education were obtained by questionnaire, while history of growth and development monitoring was obtained by KMS. Analysis through Chi-Square test and risk value test. Results: The results showed that there was a relationship between stunting and a history of exclusive breastfeeding (p=0.000; OR=0.146; CI95%=0.057-0.377), family income per capita (p=0.025; OR=0.395, CI95%=0.174-0.898); and mother's education (p=0.013, OR=0.308, CI95% =0.119-0.797). However, there was no relationship between stunting and a history of acute diarrhea (p=0.094; OR=2.037; CI95%=0.882-4.706) and a history of growth monitoring (p=0.161; OR=0.443; CI95%=0.139–1.409). Conclusion: Toddlers without exclusive breastfeeding, having a history of acute diarrhea, low family income per capita, low maternal education, and a history of poor growth monitoring, have a greater risk of experiencing stunting.